How Single-Molecule Localization Microscopy Expanded Our Mechanistic Understanding of RNA Polymerase II Transcription - Hoboth, Peter; Šebesta, Ondřej; Hozák, Pavel (International journal of molecular sciences, 2021)
Classical models of gene expression were built using genetics and biochemistry. Although these approaches are powerful, they have very limited consideration of the spatial and temporal organization of gene expression. Although the spatial organization and dynamics of RNA polymerase II (RNAPII) transcription machinery have fundamental functional consequences for gene expression, its detailed studies have been abrogated by the limits of classical light microscopy for a long time. The advent of super-resolution microscopy (SRM) techniques allowed for the visualization of the RNAPII transcription machinery with nanometer resolution and millisecond precision. In this review, we summarize the recent methodological advances in SRM, focus on its application for studies of the nanoscale organization in space and time of RNAPII transcription, and discuss its consequences for the mechanistic understanding of gene expression.
Keywords: genetická transkripce; Microscopy, Fluorescence; RNA Polymerase II; cell nucleus; photoactivation; Humans; zobrazení jednotlivé molekuly; gene expression; super-resolution microscopy; regulace genové exprese; Transcription Factors; stochastic optical reconstruction; Protein Binding; Transcription, Genetic; transcription foci; fluorescenční mikroskopie; lidé; Single Molecule Imaging; zvířata; stimulated emission depletion; structured illumination; transcription factors; RNA-polymerasa II; Gene Expression Regulation; vazba proteinů; transkripční faktory; Animals